Constraints on the preservation of proxy data in carbonate archives – lessons from a marine limestone to marble transect, Latemar, Italy. Issue 2 (8th October 2021) - Mueller, Mathias; Jacquemyn, Carl; Walter, Benjamin F.; Pederson, Chelsea L.; Schurr, Simon L.; Igbokwe, Onyedika A.; Jöns, Niels; Riechelmann, Sylvia; Dietzel, Martin; Strauss, Harald; Immenhauser, Adrian
Abstract: This work evaluates an exceptionally complex natural laboratory, the Middle Triassic Latemar isolated platform in the northern Italian Dolomite Mountains and explores spatial and temporal gradients in processes and products related to contact metamorphism, dolomitization and dedolomitization of marine limestones. The relation between petrographic change and re‐equilibration of geochemical proxy data is evaluated from the perspective of carbonate‐archive research. Hydrothermal dolomitization of the limestone units is triggered by dykes and associated hydrothermal fluids radiating from the nearby Predazzo Intrusion. Detailed petrography, fluid inclusion analysis, δ 13 C and δ 18 O data and 87 Sr/ 86 Sr isotope ratios shed light on the extreme textural and geochemical complexity. Metamorphic and diagenetic patterns include: (i) peak‐metamorphic and retrograde‐metamorphic phases including three dolomite marbles, two dedolomite marbles, brucite, magnesium silicates and late‐stage meteoric/vadose cement at the contact aureole; (ii) four spatially defined episodes of dolomitization, authigenic quartz, low magnesium calcite and late‐stage meteoric cement at the Latemar isolated platform; and (iii) kilometre‐scale gradients in δ 13 C values from the contact aureole towards the platform interior. Results shown here are relevant for two reasons: first, the spatial analysis of alteration products ranging from high‐grade metamorphic overprint of marbles at temperatures of 700°C in the contact aureole to moderately altered limestones in the platform interior at temperatures <100°C, allows the observation of processes that commonly occur along vertical (prograde) gradients from shallow burial to metamorphism at depths >20 km. Second, under rock‐buffered conditions, and irrespective of metamorphic to diagenetic fluid−rock interactions, both marbles, and low‐temperature hydrothermal dolomites have conservative marine δ 13 C and δ 18 O values. The fact that metamorphism and hydrothermal dolomitization of precursor limestones and early diagenetic dolostones did not per se reset environmental proxy data is of interest for those concerned with carbonate archive research in Earth's deep time.